The Perception of the Academic Community in Buying Halal Labeled Drugs - Fajar Ira Juwita; Chotijatun Nasriyah; Yuda Jatnika (GLOBAL HEALTH SCIENCE GROUP, 2021)
Drugs, traditional medicines and cosmetics, are declared halal if they already include halal labels on their package. Halal labeling on drugs must pass the procedures that are in compliance with halal product guarantee law. This objective of this study is to identify the perception of the academic community of STIKES Notokusumo towards the purchase of drugs that include halal labels. This study is a descriptive study with a simple random sampling and obtained by 102 respondents. The data retrieval obtained using the questionnaire and statistic analyzed. The majority of the academic community of STIKES Notokusumo has known the drug products consumed can be seen through halal labels on drug packaging. The majority of the academic community also agrees that all halal-labeled drug and food products must be in compliance with the law and only certain institutions are able to issue halal label certification, and the products certified halal by the Indonesian Ulema Council will be guaranteed halal.